Efectos del inoculante Rhizocaj (Rhjzobium laponicum) sobre el rendimiento de Soya “Glvcine máx. (L) Merril” variedad cristalina en el Distrito de Morales - Reyes Avalos, Alex Germán (2002)
With the aim(lens) to evaluate different doses of the lnoculante Rhizocaj with Vine-stock You Knock down "61" of the bacterium (Rhizobium japonicum) to determine the effects on the yield of grain of Soy bean and to determine the relation benefit - cost of the best treatment There was realized a comparative test(essay) of 6 treatrnents. where a maximurn yield of grain was reached with T4 (3757 53 Kg/ha) followed(continued) of T3 (3678.12 Kg/ha). The experiment 1 carry out in the Sector Oasis, district of Mulberry trees(moralities), province of St Martin, Region St Martin, in a soil that has the following characteristics: texture sandy Franc, pH = 6 98, rich in potassium (0 .5 meq/100 gr.), High phosphorus (27 O ppm) and average nitrogen. The experimental disposition(regulation) employee was of block Completely Randomizado with six treatments and four repetitions, four ruts for every unit, separated of 0.60m between(among) rows and 0.25 m between(among) plants(floors). obtaining a population of 133332 plants(floors)/ha equivalently to 45 Kg. Of [Attention l Seul le début de votre texte a été traduit] Before the sowing the seed was inoculated with the lnoculante Rhizocaj with Vine-stock You Knock down "61" of agreement to every dosing and later one proceeded to sow. To the four the week there was done the first evaluation of the quantity of nodules by plant(floor) and the second evaluation was realized to the filling pod where a major(b'1gger) number of nodules was obtained in the roots by a major(bigger) activity of the bacterium. In all the treatments a major(bigger} production superior(top) was observed to the witness.